Variação temporal na dieta e na abundância de Helmintos do Lagarto-de-Cauda Espinhosa Strobilurus torquatus Wiegmann, 1834 (Squamata:Tropiduridae) na Mata Atlântica, Nordeste da Região Neotropical - SILVA, Giovana Dias (2022)
ABSTRACT: Spatial and temporal variations can influence the abundance and biology of parasite species and even the transmission process, in addition to influencing the diet, reproduction and distribution of hosts. We studied the seasonal influence on the diet and endoparasites of the lizard Strobilurus torquatus. The data used in the present work were obtained from the samples of the research project <Ecological Liberation of Lizards and Endoparasites in the Tropical Atlantic Forest, Northeast of the Neotropical Region=. The lizards were collected in the Engenho Gargaú Private Natural Heritage Reserve located in the municipality of Santa Rita, in the state of Paraíba. Thirty-three lizards were analyzed, of which 30 were parasitized (general prevalence of 90%), with the helminth species Physaloptera lutzi (69,6%), Spauligodon loboi (51,5%), Strongyluris oscari (15,1%) and Haplometroides odhneri (3,03%). Our analysis showed that endoparasite abundance was influenced by host body mass (R2m: 0.95; R2 c: 0.95; z-value: -7.485; p < 0.0001) and host body size (R2m: 0.95; R2 c: 0.95; z-value: 11.521; p < 0.0001), indicating that larger hosts harbored more parasites. Indicating that larger hosts harbored more parasites. In addition, we observed a variation in relation to sex with males being more parasitized than females. When comparing the two seasons (dry and rain) we observed that the greatest abundance of endoparasites occurred during the rainy season. Regarding diet, we did not find significant variation between sexes. The same was observed when comparing diet data between seasons, showing a high niche overlap, which indicates that male and female specimens of S. torquatus consumed practically the same prey during the analyzed period. The influence of host sex on the abundance of endoparasites may be due to the more territorial behavior exercised by males. The increase in parasite abundance during the rainy season may be related to the life cycle of the species found, since the species found (P. lutzi, S. loboi, S. oscari and H. odhneri) reach better conditions with the increase in humidity in the environment.